Environmental Conservation Education through Biopore Introduction for Elementary School Students at Sanggar Belajar Kuala Lumpur - Handajani, Mudjiastuti; Rohadi, Rohadi; Pramucitra, Sinta Pramucitra; Pinandita, Satria; Anwar, Nik Syahrim Nik (Universitas Negeri Semarang, 2025)
As the capital of Malaysia, Kuala Lumpur has not escaped various environmental issues that have worsened due to rapid urbanization, ranging from air pollution to insufficient waste management. This condition requires a creative solution to foster awareness of sustainability from a young age. In response, a community service program titled